1986
DOI: 10.1128/jcm.24.4.657-660.1986
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of toxicity and enhanced cytomegalovirus detection in cell cultures inoculated with semen from patients with acquired immunodeficiency syndrome

Abstract: Although semen is a particularly rich source of cytomegalovirus (CMV) and is useful for monitoring CMV shedding, its culturing is associated with extensive monolayer toxicity, isolation failures, and lengthy detection times. Inoculation of fractionated semen with immunoperoxidase staining of monolayers eliminated virtually all toxicity, increased isolation rates and monolayer infectivity, and greatly reduced detection times. Semen specimens (n = 73) were processed conventionally (C) or separated into supernata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…As in the case of semen, CMV shedding is at low or undetectable levels in urine and throat washings of heterosexual males (5,10,12). Isolation of CMV from these three types of clinical specimens has been much higher in homosexual men with overt AIDS, with prevalence rates ranging from 68 to 100% (23,32,40). The present investigation showed that the prevalence of shedding of CMV in semen is closely associated with HIV serostatus in homosexual and bisexual men who did not have AIDS.…”
Section: Discussionsupporting
confidence: 44%
“…As in the case of semen, CMV shedding is at low or undetectable levels in urine and throat washings of heterosexual males (5,10,12). Isolation of CMV from these three types of clinical specimens has been much higher in homosexual men with overt AIDS, with prevalence rates ranging from 68 to 100% (23,32,40). The present investigation showed that the prevalence of shedding of CMV in semen is closely associated with HIV serostatus in homosexual and bisexual men who did not have AIDS.…”
Section: Discussionsupporting
confidence: 44%
“…Improved isolation rates and more rapid results for HSV and CMV have been reported (Gleaves et al, 1984(Gleaves et al, , 1985aSalmon et al, 1986). Fractionation of semen with inoculation of the pellet fraction into culture has been associated with elimination of monolayer toxicity and enhanced CMV detection in AIDS patients (Howell et al, 1986).…”
Section: Specimen Processingmentioning
confidence: 99%